2017
DOI: 10.1080/13697137.2017.1392501
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of age at menopause in women with polycystic ovary syndrome

Abstract: These findings provide the insight that, as reflected through significantly higher average levels of AMH in PCOS women, their predicted reproductive lifespan could be 2 years longer than their normo-ovulatory counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 32 publications
3
26
0
2
Order By: Relevance
“…17,26,27 The postulated menopausal age of women with PCOS, based on AMH, was approximately 2 years later than that of controls. 27 This is in line with our findings of the verified menopausal age, based on medical history and biochemistry.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…17,26,27 The postulated menopausal age of women with PCOS, based on AMH, was approximately 2 years later than that of controls. 27 This is in line with our findings of the verified menopausal age, based on medical history and biochemistry.…”
Section: Discussionmentioning
confidence: 79%
“…23 The majority of the women had undergone ovarian surgery, including wedge resection, which reduced the ovarian reserve and had plausible secondary consequences for menopausal age. 17,26,27 The postulated menopausal age of women with PCOS, based on AMH, was approximately 2 years later than that of controls. It was found that a self-reported PCOS diagnosis was independently associated with delayed menopause, which is in line with the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Слід зазначити, що за даними окремих досліджень, вік менопаузи в жінок із СПКЯ є більшим порівняно з жінками без СПКЯ, вірогідно внаслідок високих рівнів антимюллерового гормону (АМГ) [36,37]. У дослідженні Y.S.…”
Section: особливості синтезу андрогенів в менопаузіunclassified